Assessing the quality of life of patients with intestinal failure on home parenteral nutrition. - Richards, D M (1997)
BACKGROUND: A study was performed to measure the quality of life of patients receiving home parenteral nutrition (HPN). Quality of life is an important determinant of the effectiveness of health technologies, but it has rarely been assessed in patients receiving HPN. AIMS: To measure quality of life and highlight any moderating factors. PATIENTS AND METHODS: Quality of life was measured using two validated instruments (SF 36 and EuroQol) in 51 patients with intestinal failure. All patients had benign disease, the commonest being Crohn's disease (n = 35). RESULTS: HPN patient scores were worse for six of eight SF 36 domains (p < 0.05) compared with standard population scores. Younger patients (< 45) had good scores but older patients (> 55 years) scored significantly less. Patients addicted to narcotic substances had very low scores. EuroQol utility scores confirmed the SF results. Forty one patients reported that they felt too ill to work and only five were in full time work or education. CONCLUSIONS: The health status profile of our young patients on HPN was good compared with the normal population. The poorest scores were in older patients and those dependent on narcotic drugs. This has clinical and economic relevance when considering such patients for HPN.